Modeling Impacts of Policing Initiatives on Drug and Criminal Careers of Arrestees in New York City, New York, 1999 - Johnson, Bruce D. ([Verlag nicht ermittelbar], 2003)
This study sought to understand the accuracy and validity of arrestee self-reports of drug use and the overall contact of arrestees with the criminal justice system, with a secondary focus on how arrestee self-reports of drug use correspond to urinalysis results. Moreover, this study investigated whether arrestees were aware of the New York City Police Department's Quality-of-Life (QOL) policing efforts and whether they had changed their criminal behavior as a result. A QOL Policing Supplement, designed to explore new means of evaluating police behavior, was administered to all adult arrestees in the five boroughs of New York City (Bronx, Brooklyn, Manhattan, Staten Island, and Queens) who had completed an Arrestee Drug Abuse Monitoring (ADAM) program interview, provided a urine specimen, and were willing to answer additional questions concerning QOL policing. Part 1, Policing Study Data, is a large integrated dataset containing all of the variables derived from the 1999 ADAM interviews, the Policing Supplement instrument, and administrative records data from the Criminal Justice Agency (CJA) and the New York State Division of Criminal Justice Services. This dataset is linked, via an anonymous case number, to Part 2, Arrestee Criminal History Data, which contains each arrestee's official criminal history.